Two-Dimensional Nanosheet-Based Photonic Nanomedicine for Combined Gene and Photothermal Therapy - Kim, Na Yoon; Blake, Sara; De, Diba; Ouyang, Jiang; Shi, Jinjun; Kong, Na (Frontiers in Pharmacology, 2020)
Two-dimensional (2D) nanosheets are characterized by their ultra-thin structure that set them apart from their bulk materials. Due to this unique 2D structure, they have a high surface-to-volume ratio that can be beneficial for delivery of various drugs including therapeutic DNAs and RNAs. In addition, various 2D materials exhibit excellent photothermal conversion efficiency when exposed to the near infrared (NIR) light. Therefore, these 2D nanosheet-based photonic nanomedicine have been gaining tremendous attention as both gene delivering vehicles and photothermal agents, which create synergistic effects in the treatment of different diseases. In this minireview, we briefly provide an overview of the following two parts regarding this type of photonic nanomedicine: (1) mechanism and advantages of nanosheets in gene delivery and photothermal therapy, respectively. (2) mechanism of synergistic effects in nanosheet-mediated combined gene and photothermal therapies and their examples in a few representative nanosheets (e.g., graphene oxide, black phosphorus, and translational metal dichalcogenide). We also expect to provide some deep insights into the possible opportunities associated with the emerging 2D nanosheets for synergistic nanomedicine research.